Bioactive phenolic compounds from the agroindustrial waste of colombian mango cultivars ‘sugar mango’ and ‘tommy atkins’—an alternative for their use and valorization (2019)
The aim of this study was to explore the potential of the agroindustrial waste from two Colombian mango cultivars as sources of bioactive phenolic compounds. Phenolic extracts from mango waste (peels, seed coats, and seed kernels) of ‘sugar mango’ and ‘Tommy Atkins’ cultivars were obtained. The bioactive properties of the phenolic extracts were accessed by measuring their free radical scavenging activity and antioxidant effects against lipid oxidation in food products; moreover, their antiproliferative effects against some cell lines of human cancer were explored. It is observed that the agroindustrial waste studied provides promising sources of bioactive phenolics. ‘Sugar mango’ waste provided extracts with the highest antioxidant effect in food products and antiproliferative activity; these extracts reduced lipid oxidation and cell growth by more than 57% and 75%, respectively. The seed kernel from ‘sugar mango’ supplied the extract with the best bioactive qualities; in addition, some recognized bioactive phenolics (such as mangiferin and several galloyl glucosides) were observed in this extract and related with its properties. The results obtained suggest that ‘sugar mango’ waste may be considered a source of bioactive phenolics, with promising uses in food and pharmaceutical products. Thus, a suitable alternative for the use and valorization of agroindustrial waste from Colombian mango cultivars is presented.